Perlakuan Akuntansi Kas Kecil - Dwi Suranti (Journal of Applied Accounting and Taxation, 2016)
This research was conducted at calibration service company for measuring instrument engaged in calibration of measuring instruments. In this study, the authors take the point about how little cash management at company. Formation of petty cash at company aims to finance companies that nature needs a relatively small expenditure. Petty cash management at company has been said to be good, the duties and functions of each part and also the control of petty cash at company so petty cash can be maintained and monitored.